Ferro Content in Soil and Mustard Leave (Brassica Junjea) Treated by Agricultural Waste on the Biosensitizer-Iron Photoreduction - Johnly Alfreds Rorong; . Sudiarso; Budi Prasetya; Jeany Polii Mandang; Edi Suryanto Suryanto (JOURNAL OF TROPICAL SOILS, 2012)
Atom absorption spectrophotometer (AAS) had been used to analyzed Ferro in the soil and in the green mustardleaf (Brassica junjea) treated with phenolics extract from the agricultural wastes of clove leaf (Eugenia aromatica),rice straw (Oryza sativa) and water hyacinth leaf (Eichhornia crassipessolms), in which the phenolics as the electrondonor on the biosensitizer – iron photoreduction. Phenolics extract was obtained from varions of aquadest and 40;60; 80% methanol. The solution without extract was used as sensitizer, while the extract without illumination wasused as control. Green mustard was packed into medium polybag within it added by 2,000 mg kg-1. Soil type assample was volcanic soil in various categories, such as: soil-extract, soil NPK fertilizer extract, and soil control.Results of Ferro analysis in the clove leafs treated with 80% methanol indicated the highest increasing Fe2+ of 22.94mg kg-1. Rice straw treated with 60% methanol showed the highest increasing Fe2+ of 34.5 mg kg-1. The waterhyacinth leafs treated with 60% methanol obtained the highest increasing Fe2+ of 17.67 mg kg-1. Fe2+ concentrationat soil-clove leafs had the highest increasing of Fe2+ production for 5.6 mg kg-1. Its concentration at soil NPKfertilizer extract water hyacinth leafs showed the highest increasing of Fe2+ production for 13.39 mg kg-1. Highestconcentration of Fe2+ in the green mustard at soil NPK fertilizer extract clove leafs was 176.37 mg kg-1. Variousconcentrations and various soil categories resulted in the highest increasing Fe2+ concentration in each agricultural waste extract.Keywords: Agricultural waste extract; ferro analysis; iron photoreduction; soil category[How to Cite: Rorong JA, Sudiarso, B Prasetya, J Polii-Mandang and E Suryanto. 2012. Ferro Content in Soil and Mustard Leave (Brassica junjea) Treated by Agricultural Waste on the Biosensitizer-Iron Photoreduction. J Trop Soils, 17 (3): 211-218. doi: 10.5400/jts.2012.17.3.211][Permalink/DOI: www.dx.doi.org/10.5400/jts.2012.17.3.211]